Evaluation of semicarbazones for anticonvulsant and sedative-hypnotic properties - Pandeya S.N.; Aggarwal N.; Jain J.S. (My University, 2025)
A series of semicarbazones and thiosemicarbazones were synthesized and evaluated for anti-convulsant activity. Some compounds provided significant protection against Maximal Electroshock (MES) and subcutaneous strychnine induced seizures. Compound 1 was the most active in the series with activity in a dose of 30 mg/kg in the strychnine seizure pattern test and an ED50 of 10 mg/kg in the MES test. Hence it could serve as a prototype molecule for future development. Also compounds with a p-nitrophenyl substitution in place of the amino hydrogen of semicarbazone moiety showed activity in a dose of 30 mg/kg and an ED50 of 83 mg/kg in the MES test.